If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + 3m) = 42 (5 * 3 + 3m * 3) = 42 (15 + 9m) = 42 Solving 15 + 9m = 42 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 9m = 42 + -15 Combine like terms: 15 + -15 = 0 0 + 9m = 42 + -15 9m = 42 + -15 Combine like terms: 42 + -15 = 27 9m = 27 Divide each side by '9'. m = 3 Simplifying m = 3
| r(r+5)-104=0 | | 7x+7+14+110=180 | | 37-10a=51+6a | | 2(3x-1)=2x+10 | | x(3x-1)=310 | | 9(7-2x)=12(2+5) | | 3x*2+23x-8=0 | | 2x/3=(x/6)+1 | | 4u^3w^4/2u^4y^3-10u^2 | | (-6.8)+(-1.9)= | | -9k+4+7k=23 | | 1/3(9x+14)+1/3 | | (-1)+11+5= | | ln(3n+7)=ln(-3n-5) | | x^2-x-8=65 | | (B-2)+(B)+(B*4)=26 | | y=1/2*4.5+4 | | (x+3)(x-3)-40=0 | | y=1/2x*4.5+4 | | 20/3^2+4-2^3 | | -3(-1)(-2)(5)= | | y^2+12=-64 | | x^2-5x=66 | | 2x+x-10=0 | | -2x-8=-15x^2 | | 0.33f-6=-8 | | -3(a+3)-6=2(4a+5)+8 | | (x+3)(x-3)-16=0 | | (B-2)+(B)+(B+3)=25 | | 6-1/4=C | | -8+x=-4+0 | | ln(x+9)-ln(x-9)= |